RESEARCH ON THE APPLICATION DESIGN OF NEW MEDIA IN MODERN MUSEUM INTERIOR DISPLAY - Косенко, Данило; Цуй, Сіна (SWorldJournal, 2023)
This paper introduces the research results of new media application design in modern museum interior display. The purpose is to explore a feasible use of new media technology to better promote the exchange and mutual learning of human civilization museum